POST STROKE DEPRESSION AND ANXIETY: PREVALANCE AND CORRELATES - NOUSHAD, NASMI; S, SACHITA; VARUGHESE, SHILPA ANNA; K JOY, SIJIMOL; JOSE, SNEHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of the study is to evaluate the prevalence of depression and anxiety in post-stroke patients and identify its predictors. Materials and Methods: This study was conducted for a period of 6 months among 81 patients admitted with stroke in SSIMS and RC, Davangere. The information compiled from patient data collection form was assessed for comorbid conditions and type of stroke. Assessment for depression and anxiety was conducted using Hamilton D (HAM-D) and HAM-A scale and information of location of lesion was obtained from patient’s neuroimaging results. Quality of life (QOL) of post-stroke was assessed using stroke and aphasia QOL (SAQOL) questionnaire. Follow-up was conducted for patients who were diagnosed with depression and anxiety within 1 to 3 months. Results: Depression was more prevalent as compared to anxiety in post-stroke patients and was predominant in males and between the ages 61 and 70 years. Hypertension and diabetes were found to be a major comorbid conditions in such patients. Factors contributing to increased risk of depression and anxiety after stroke include age, sex, comorbidities, lesion location, and type of stroke. Post-stroke depression (PSD) and anxiety showed statistically significant association with left-sided lesion. Conclusion: PSD and anxiety are a relatively common complications and can result in poor QOL in stroke patients. Early detection of depression and anxiety symptoms may assist functional recovery and improve QOL in stroke patients. Careful evaluation of PSD and post-stroke anxiety should be integrated into clinical care of stroke patients.